Shock Boundary Layer Interaction and Aero-Optical Effects in a Transonic Flow over Hemisphere-on-Cylinder Turrets - Xiang Ren; Huahua Yu; Xianghong Yao; Hua Su; Peng Hu (International Journal of Aerospace Engineering)
Hemisphere-on-cylinder turrets are the main airborne optical platform structure. However, an unsteady shock boundary layer interaction (SBLI) would act on flow separation and turbulent wake, which causes serious aero-optical effects with high spatial and temporal frequency characteristics. In this paper, the SBLI phenomenon of a hemisphere-on-cylinder turret is recorded in a wind tunnel at Ma=0.7 using shadowing and Mach-Zehnder interferometer measurements. Its wavefront distortion is measured using the Shack-Hartmann measurement. The detached eddy simulation (DES) based on SST k-ω turbulence model and ray-tracing methods are used to reproduce the transonic flow and optical aberration. Experiments and simulations suggest that the SBLI causes the flow to separate earlier relative to a subsonic flow over the turret. The time-averaged root-mean-square of optical path difference (OPD) over the beam aperture is 0.56 λ∼0.59 λ with λ as the wavelength, while the root-mean-square of the time-averaged OPD is about 0.45 λ. The local shock and wavefront distortion have dual peak frequencies at StD=fD/U∞=0.24 and 0.34, different from the single-peak-frequency phenomenon of a subsonic flow over turrets. Fast model decomposition of wavefront can be performed by proper orthogonal decomposition (POD) of its Zernike coefficients. The first two modes contain the shock’s reciprocating motion.